VWF, CXCL8 and IL6 might be potential druggable genes for acute coronary syndrome (ACS). (December 2019) - Gu, Jinxia; Zhu, Hong; Zhu, Dayong; Li, Ming; Xiao, Mochao; Yan, Dongxia; Shen, Shaohui
Graphical abstract: Highlights: IL6 and VEGFA played major roles in ACS. Hsa-miR-29 and hsa-miR-1 might be associated with ACS progression. NFIC, NFKB1 and RELA might be critical transcription factors related to ACS. VWF, CXCL8 and IL6 might be potential druggable genes for ACS therapy. Abstract: Objective: Acute coronary syndrome (ACS) is currently a leading cause of morbidity and mortality worldwide. This study aimed to screen critical genes and miRNAs involved in ACS. Materials and methods: Microarray data (access number GSE19339) was downloaded from Gene Expression Omnibus (GEO) database. After data preprocessing, we screened the differentially expressed genes (DEGs) using limma package and subsequently performed enrichment analysis using DAVID tool. The protein-protein interaction (PPI) network and transcription factor (TF)-miRNA-target gene regulatory network were visualized using Cytoscape software. Finally, the drug-gene interactions were predicted using DGIdb database. Results: A total of 425 DEGs were identified in ACS samples compared with healthy control samples. Functional enrichment analysis showed that DEGs were mainly involved in angiogenesis, inflammatory response and PI3K-Akt signaling pathway. IL6 and VEGFA were key nodes in PPI network. In addition, hsa-miR-29, hsa-miR-1, NFIC, NFKB1 and RELA were identified as key factors in TF-miRNA-target gene network. Finally, the prediction results revealed that VWF, CXCL8 and IL6 had higher degree than other genes. Conclusion: IL6 and VEGFA might play major roles in ACS progression. Two miRNAs ( hsa-miR-29 and hsa-miR-1 ) and three TFs ( NFIC, NFKB1 and RELA ) were critical genes involved in pathological process of ACS. VWF, CXCL8 and IL6 might be potential druggable genes for ACS therapy.